The predictors of successful methotrexate treatment of tubal ectopic pregnancy - Eiman Abdelfattah-Arafa; Hager Farag Abdussalam; Mohamed Omar Saad; Walid El Ansari (Taylor & Francis Group, 2024)
Background The pre-treatment characteristics of the patient and ectopic pregnancy to determine the patients who are likely to successfully respond to methotrexate (MTX) therapy remain controversial. This study investigated the outcomes of ectopic pregnancy after one and two MTX doses and their independent predictors.Methods Retrospective cross-sectional study of women who consented to MTX treatment in 2017-2018 at our institution (N = 317). Of these, patients with Caesarean scar pregnancies were excluded because they require different treatment protocols (n = 25). All patients were treated according to our institution's protocol based on international guidelines and standardised across the three hospitals included in the current study. We retrieved patients' demographics, laboratory, ultrasonography, and clinical characteristics from our hospital database. Serum β-human chorionic gonadotropin (β-hCG) was measured using electrochemiluminescence immunoassay; ectopic pregnancy was diagnosed using ultrasonography (transvaginal probe).Results Two ninety-two patients were included in the current analysis. Age, pre-treatment β-hCG levels, sonographic presence of yolk sac, presence of foetal cardiac activity, and pelvic pain were significantly different between patients with successful and unsuccessful outcomes. Younger age (adjusted odds ratio [aOR] 2.33, 95% confidence interval (CI) 1.16-4.66, p = .017), no pelvic pain (aOR 2.65, 95%CI 1.03-6.83, p = .043), lower initial β-hCG level (aOR 1.32, 95%CI 1.08-1.59, p = .005), and absence of foetal cardiac activity (aOR 12.63; 95% CI 1.04-153.6; p = .047) were independently associated with success. Treatment failure odds were >2 folds higher for each 10-year age increase (p = .017), 32% higher for each 1000 IU/L increase in initial β-hCG level (p = .005), and >2 folds higher in presence of pelvic pain (p = .043).Conclusions MTX is effective in most patients, averting invasive surgery, which might affect fertility. Pre-treatment β-hCG levels, age, pelvic pain, and foetal cardiac activity was independently associated with outcomes. Research should assess the relationship between the ectopic pregnancy size and treatment outcomes and refine β-hCG titres where treatment would be ineffective.